The impact of in utero nutritional programming on small ruminant performances - Ashworth C.J.; Dwyer C.M.; McEvoy T.G.; Rooke J.A.; Robinson J.J. (Nutritional and foraging ecology of sheep and goats, 2009)
The current resurgence of interest in foetal programming of post-natal production traits in small ruminants, notably sheep, is embracing reproductive performance, behaviour and the development of the immune system. It is also posing questions regarding effects on appetite and longevity. The earlier known effects on wool production and carcass composition are being revisited. Much emphasis is being placed on understanding the cellular and molecular mechanisms that are involved, in particular the alterations in the expression of genes involved in prenatal growth and development. Unlike the early studies in which the emphasis was on altered nutrition during the foetal stages of development, it is the pre-implantation embryo that is now attracting attention. The findings are demonstrating the exquisite sensitivity of the early cleavage stage embryo to its environment with permanent carryover effects on the new-born and adult. Nonetheless more quantitative data are required to estimate the economic impact of in utero programming in commercial sheep and goat production systems. It is suggested that in farming practice, some of the most important effects of in utero nutritional programming may be those relating to behaviour and immune competence with the associated production and product quality benefits coming from improvements in health and welfare.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)